Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\left(2x-1\right)^{10}=\left(2x-1\right)^{11}\)
\(\Leftrightarrow\orbr{\begin{cases}2x-1=1\\2x-1=0\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=1\\x=\frac{1}{2}\end{cases}}\)
Vậy ...........
\(\Rightarrow\left(2x-1\right)^{11}-\left(2x-1\right)^{10}=0\)
\(\Rightarrow\left(2x-1\right)^{10}.\left[\left(2x-1\right)-1\right]=0\)
\(\Rightarrow\orbr{\begin{cases}\left(2x-1\right)^{10}=0\\\left(2x-1\right)-1=0\end{cases}\Rightarrow\orbr{\begin{cases}2x-1=0\\2x-1=1\end{cases}}}\)
\(\Rightarrow\orbr{\begin{cases}x=\frac{1}{2}\\x=1\end{cases}}\)
Vậy \(x\in\left\{\frac{1}{2};1\right\}\)
a) 2x.(1 + 23) = 144
2x . 9 = 144
2x = 16
=> x = 4
b) (2x - 1)10 = (2x - 1)100
(2x - 1)100 - (2x - 1)10 = 0
(2x - 1)10.[ (2x - 1)90 - 1] = 0
=> (2x - 1)10 = 0 hoặc (2x - 1)90 - 1 = 0
=> 2x = 1 hoặc (2x - 1)90 = 1
=> x = \(\frac{1}{2}\) hoặc \(2x-1=\orbr{\begin{cases}1\\-1\end{cases}}\)
=> \(2x=\orbr{\begin{cases}2\\0\end{cases}}\)
=> x = {\(\frac{1}{2};1;0\)}
1) =>2x+4+4+x=11
=>2x+4+4+x-11=0
=>3x-3=0
=>3x=3
=> x=1
Vậy x thuộc {1}
2)=>x+x+1+2x+4=3
=>x+x+1+2x+4-3=0
=>4x+2=0
=>4x=-2
=>x=-2/4
=>x=-1/2
Vậy x thuộc {-1/2}
\(\left(2x-1\right)^{10}=\left(2x-1\right)^{11}\)
\(\Leftrightarrow\orbr{\begin{cases}2x-1=0\\2x-1=1\end{cases}\Leftrightarrow\orbr{\begin{cases}2x=1\\2x=2\end{cases}\Leftrightarrow}\orbr{\begin{cases}x=\frac{1}{2}\\x=1\end{cases}}}\)
(2x-1)10 = (2x-1)11
(2x-1)10-(2x-1)11=0
(2x-1)10.[1-(2x-1)1 ]=0
\(\Rightarrow\orbr{\begin{cases}\left(2x-1\right)^{10}=0\\1-\left(2x-1\right)^1=0\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}2x-1=0\Rightarrow2x=1\Rightarrow x=\frac{1}{2}\\2x-1=1\Rightarrow2x=2\Rightarrow x=2:2=1\end{cases}}\)
Vậy \(x\in\left\{\frac{1}{2};1\right\}\)